Sexual Behavior and HIV / AIDS Prevention in Male Sexual Men (MSM) in Denpasar City - Luh Gede Pradnyawati; Ni Made Hegard Sukmawati (WMJ (Warmadewa Medical Journal), 2021)
HIV / AIDS cases among MSM (male sex men) in Indonesia from year to year have increased significantly. Meanwhile, Bali is a province with many HIV / AIDS cases, where Denpasar is the city with the highest number of MSM. There has never been a report on sexual behavior and HIV / AIDS prevention among MSM in Denpasar. Therefore, the researchers wanted to explore the problems of sexual behavior and its prevention in MSM in Denpasar. Purpose: This study aims to obtain a vision of sexual behavior and HIV / AIDS prevention among MSM groups in Denpasar City. This study used a qualitative design with a phenomenological approach to digging deeper into sexual behavior and HIV / AIDS prevention among MSM in Denpasar City. The selection of informants in this study was taken using convenience sampling technique and conducted in-depth interviews with 10 MSM who were productive and communicative in Denpasar. After collecting data in the field, the data will be analyzed thematically. In sexual intercourse behavior, most of the MSM prioritized variations and sensations during sexual intercourse to get sexual satisfaction, such as having group sex, using arousal-enhancing drugs, and violence engaging during sexual intercourse. Some of the informants only had one permanent sexual partner. However, there are still MSM who have more than one sexual partner and receive payment for sexual intercourse. Informants use condoms in sexual intercourse and with the PrEP method to avoid HIV / AIDS. It is necessary to conduct education and counseling on sexual orientation for the community, especially for adolescents looking for identity, educating MSM to reduce high-risk behavior during sexual intercourse. Keywords: Sexual behavior, MSM, prevention, HIV / AIDS, Denpasar